Beta-adrenergic receptor agonist decreases VEGF levels through altered eNOS and PKC signaling in diabetic retina - Jiang, Youde (Growth Factors, 2015)
Vascular endothelial cell growth factor (VEGF) is increased in diabetic macular edema. Compound 49b, a novel β-adrenergic receptor agonist, is protective in a type 1 diabetic rat model. We questioned whether Compound 49b could decrease VEGF levels, suggesting that Compound 49b may be effective against edema. Two-month diabetic rats received topical Compound 49b for 7 days only and/or insulin-like growth factor binding protein 3 (IGFBP-3) siRNA. We also measured endothelial nitric oxide synthase (eNOS) and protein kinase C (PKC)ζ and PKCδ phosphorylation. Retinal endothelial cells (RECs) cultured in high glucose were treated with Compound 49b and IGFBP-3 siRNA for evaluation of the same signaling pathways. Compound 49b significantly decreased VEGF through increased IGFBP-3 in the diabetic retina. Compound 49b also reduced eNOS, PKCζ and PKCδ phosphorylation in the diabetic retina and REC. Compound 49b regulated a number of proteins involved in REC barrier properties.